Transformation of Public Services: Integration of Village Management Information System (SIMANDE) for Improved Public Services - Syariffah Alvitara Udini; Erimson Siregar; Hery Dian Septama; Rangga Firdaus (Sagamedia Teknologi Nusantara, 2023)
The rapid advancements in Information Technology (IT) have significantly impacted the provision of public services, including at the village level. This study focuses on the implementation of the Village Management Information System (SIMANDE) in Mulya Kencana Village, aimed at improving public service efficiency. SIMANDE enables residents to apply for certifications online, eliminating the need for direct visits to the village office. Village administrators also benefit from the efficient dissemination of information. The research employed the Rapid Application Development (RAD) methodology, with MySQL as the database to ensure data security and integrity. The results show highly positive user responses, indicating that SIMANDE significantly improves public service efficiency and accessibility. This study concludes that the integration of SIMANDE is a key step toward digital transformation in village-level public services, providing substantial benefits to both residents and village officials.